Spherical Nanocrystalline Cellulose (NCC) from Oil Palm Empty Fruit Bunch Pulp via Ultrasound Assisted Hydrolysis - Zianor Azrina, Z. A.; Beg, M. D. H.; R. M., Yunus; Ridzuan, Ramli; Norhafzan, Junadi; A. K. M., Moshiul Alam (Elsevier Ltd, 2017)
Nanocrystalline cellulose (NCC) was isolated from oil palm empty fruit bunch pulp (EFBP) using ultrasound assisted acid hydrolysis. The obtained NCC was analysed using FESEM, XRD, FTIR, and TGA, and compared with raw empty fruit bunch fibre (REFB), empty fruit bunch pulp (EFBP), and treated empty fruit bunch pulp (TEFBP). Based on FESEM analysis, it was found that NCC has a spherical shaped after acid hydrolysis with the assistance of ultrasound. This situation was different compared to previous studies that obtained rod-like shaped of NCC. Furthermore, the crystallinity of NCC is higher compared to REFB and EFBP. According to thermal stability, the NCC obtained shows remarkable sign of high thermal stability compared to REFB and EFBP.